Strategies for preventing social breakdown in schools (1998)
An attempt has been made in this paper to present a model on the process of social breakdown. The model, developed by Robinson (1978) describes the gradual process of breakdown in social functioning in relation to individuals, families and schools and pays particular attention to the parts various agents of social control play in the prevention of social breakdown. Strategies developed by experts which are directed at individuals, professionals and the government for the prevention of social breakdown are recommended. Thereafter, the strengths and limitations of the strategies are discussed and a conclusion is reached that urgent social work intervention in the schools will help a great deal in preventing social breakdown in schools.